2016
DOI: 10.1039/c6ra21911j
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-induced polymerization of superabsorbent composites based on sodium humate and its urea release behavior

Abstract: This study was carried out to develop a superabsorbent composite for agriculture application, which is based on acrylic acid and sodium humate and prepared by ultraviolet-induced polymerization in the presence of crosslinker and composite initiator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Compared with U, the relative abundance of Gram-positive bacteria (Actinobacteriaa nd Firmicutes) in the soil samples with U-FS(16 %) decreased, whereas that of Gram-negative bacteria, such as Proteobacteria,A cidobacteria, Bacteroidetes, andN itrospirae, increased to different extents ( Figure 6). [26] Both Ua nd U-FS(16 %) exerted little influence on the cellular viability (Figure 7a and b). Acidobacteriaa re the dominant rhizosphere bacteria able to contributet ot he degradation of plant residues, [23] the iron cycle, [24] and photosynthesis.…”
Section: Field Testmentioning
confidence: 96%
See 2 more Smart Citations
“…Compared with U, the relative abundance of Gram-positive bacteria (Actinobacteriaa nd Firmicutes) in the soil samples with U-FS(16 %) decreased, whereas that of Gram-negative bacteria, such as Proteobacteria,A cidobacteria, Bacteroidetes, andN itrospirae, increased to different extents ( Figure 6). [26] Both Ua nd U-FS(16 %) exerted little influence on the cellular viability (Figure 7a and b). Acidobacteriaa re the dominant rhizosphere bacteria able to contributet ot he degradation of plant residues, [23] the iron cycle, [24] and photosynthesis.…”
Section: Field Testmentioning
confidence: 96%
“…Therein, ATP( [(Mg,Al) 4 (Si) 8 26 ]·n H 2 O), at ype of nanoclay formed by nanorods with average dimensions of 800-2000 nm (length) and 30-40 nm (width)] formed an anonetwork under the effect of PAM. Therein, ATP( [(Mg,Al) 4 (Si) 8 26 ]·n H 2 O), at ype of nanoclay formed by nanorods with average dimensions of 800-2000 nm (length) and 30-40 nm (width)] formed an anonetwork under the effect of PAM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective use of fertilizers is an important factor in the development of agriculture; it can ensure efficiency, a high yield, and high quality in agricultural and sideline products. However, the low utilization efficiency of fertilizers hinders their application in agriculture . In particular, phosphorus is a limiting and indispensable nutrient for the growth of organisms and plants and is an indicator of surface water quality.…”
Section: Introductionmentioning
confidence: 99%
“…reported that chitosan‐g‐poly(acrylic acid) (CTS‐PAA)/SH SAR has good biodegradable and eco‐friendly propertiesand Liu et al . reported that superabsorbent composites containing SH could be used to release fertilizer …”
Section: Introductionmentioning
confidence: 99%